2020
DOI: 10.1371/journal.pmed.1003085
|View full text |Cite
|
Sign up to set email alerts
|

Migration and first-year maternal mortality among HIV-positive postpartum women: A population-based longitudinal study in rural South Africa

Abstract: Background In South Africa, within-country migration is common. Mobility affects many of the factors in the pathway for entry to or retention in care among people living with HIV. We characterized the patterns of migration (i.e., change in residency) among peripartum women from rural South Africa and their association with first-year postpartum mortality. Methods and findings All pregnant women aged �15 years were followed-up during pregnancy and the first year postpartum in a population-based longitudinal dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Evaluations of retention in care after HIV diagnosis in lowand lower-middle-income settings also currently suggest that youth and general good health, characteristics of most women of reproductive age, are associated with worse care continuum outcomes [22][23][24][25]. Studies from several sub-Saharan African countries found higher risks of LTFU among women who were younger, had a higher CD4, and were pregnant [23,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of retention in care after HIV diagnosis in lowand lower-middle-income settings also currently suggest that youth and general good health, characteristics of most women of reproductive age, are associated with worse care continuum outcomes [22][23][24][25]. Studies from several sub-Saharan African countries found higher risks of LTFU among women who were younger, had a higher CD4, and were pregnant [23,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Other characteristics of the surveillance area include low marital rates (i.e. only 20% of conjugal couples among those 20–29 years were married), late marriages, high partnership dissolution rates among older women and younger men [ 33 35 ], multiple sexual partnerships as well as by poor knowledge and disclosure of HIV status [ 33 ]. KwaZulu-Natal Province bears the largest HIV burden in South Africa, with adult HIV prevalence in this region being 36% in 2017 [ 36 ] and disproportionate provision of HIV services particularly in poorer settings [ 37 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other characteristics of the surveillance area include low marital rates (i.e. only 20% of conjugal couples among those 20-29 years were married), late marriages, high partnership dissolution rates among older women and younger men [35], multiple sexual partnerships as well as by poor knowledge and disclosure of HIV status [34]. KwaZulu-Natal Province bears the largest HIV burden in South Africa, with adult HIV prevalence in this region being 36% in 2017 [36] and disproportionate provision of HIV services particularly in poorer settings [37][38][39].…”
Section: Methodsmentioning
confidence: 99%